Disulfide‐centered star‐shaped polypeptide‐PEO block copolymers for reduction‐triggered drug release. Issue 14 (22nd April 2014) - Chang, Xiao; Liu, Lisha; Guan, Yanfei; Dong, Chang‐Ming
ABSTRACT Disulfide‐centered star‐shaped poly(ε‐benzyloxycarbonyl‐l‐lysine)‐b‐poly(ethylene oxide) block copolymers (i.e., A2B4 type Cy‐PZlys‐b‐PEO) were synthesized by the combination of ring‐opening polymerization and thiol‐yne chemistry. Their molecular structures and physical properties were characterized in detail by FTIR, 1H NMR, gel permeation chromatography, differential scanning calorimetry, wide‐angle X‐ray diffraction, and polarized optical microscope. Despite mainly exhibiting an α‐helix conformation, the inner PZlys blocks within copolymers greatly prohibited the crystallinity of the outer PEO blocks and presented a liquid crystal phase transition behavior in solid state. These block copolymers Cy‐PZlys‐b‐PEO self‐assembled into nearly spherical micelles in aqueous solution, which had a hydrophobic disulfide‐centered PZlys core surrounded by a hydrophilic PEO corona. As monitored by means of DLS and TEM, these micelles were progressively reduced to smaller micelles in 10 mM 1, 4‐dithiothreitol at 37 °C and finally became ones with a half size, demonstrating a reduction‐sensitivity. Despite a good drug‐loading property, the DOX‐loaded micelles of Cy‐PZlys‐b‐PEO exhibited a reduction‐triggered drug release profile with an improved burst‐release behavior compared with the linear counterpart. Importantly, this work provides a versatile strategy for the synthesis of the disulfide‐centered star‐shaped polypeptide block copolymers potential for intracellular glutathione‐triggered drug delivery systems. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 2000–2010